2013
DOI: 10.3855/jidc.4110
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of real-time PCR assay targeting lipL32 gene for diagnosis of human leptospirosis in Uruguay

Abstract: Introduction: Assays based on DNA amplification can provide information that contributes to the initial management of patients with leptospirosis. However, these have not been adopted in Uruguay. Our aim was to evaluate the performance of the lipL32 real-time PCR (qPCR) for diagnosis of leptospirosis. Methodology: We analyzed by microscopic agglutination test (MAT) and lipL32 qPCR serum samples from 183 patients with suspected leptospirosis. To establish the analytical sensitivity of the qPCR, experimentally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
13
1
1
Order By: Relevance
“…PCR has more sensitivity in the first days of illness due to its ability to detect 2 -20 genomics of leptospires from sera and 10 genomics from urine (11,16). However, low positivity during the course of the disease was observed (11,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR has more sensitivity in the first days of illness due to its ability to detect 2 -20 genomics of leptospires from sera and 10 genomics from urine (11,16). However, low positivity during the course of the disease was observed (11,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…urea, creatinine, and hemoglobin derivates) that may inhibit DNA amplification with leptospiral primers (18). Moreover, other possible reasons include the absence of the organisms in the blood (26), the microbial counts of about five cells that were too low to be detected (20,26), and degradation of DNA due to prolonged sample storage and several sample thawing (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…As the latency increased, the MAT was found to be more reliable than PCR. The authors suggest that a PCR-mediated diagnosis is more useful in the first week of infection [37]. Cermakova et al [38] also reported a real-time PCR method that could detect one to five genome copies/ml of liquid biological material and differentiate pathogenic strains from nonpathogenic strains [38].…”
Section: Lipl32 In the Diagnosis Of Leptospirosismentioning
confidence: 97%
“…PCR-assisted diagnostic methods are adopted. González et al [37] developed a PCR-based diagnostic method targeting the LipL32 gene to detect leptospirosis in Uruguay. Compared with agglutination, the PCR method could detect the disease early.…”
Section: Lipl32 In the Diagnosis Of Leptospirosismentioning
confidence: 99%
“…Consequently, serotyping has resulted in the identification of over 230 different serovars among Leptospira with serovars crossing species lines [10]. The limited ability of sequencing technology at the advent of the identification and characterization of members of Leptospira was a driving force for this convention, but rapid sequencing technology such as qPCR has begun to enable scientists and clinicians to rapidly and effectively identify infecting leptospires and their phylogenetic relationships [11]. …”
Section: Introductionmentioning
confidence: 99%